2008
DOI: 10.1016/j.jfca.2007.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The Pacific Tracker (PacTrac): Development of a dietary assessment instrument for the Pacific

Abstract: The Pacific Tracker (PacTrac) is a new dietary assessment program that can be used to evaluate dietary data for nutrition studies in the Pacific Islands. PacTrac is a modification of the Interactive Healthy Eating Index (IHEI) developed by the US Department of Agriculture's Center for Nutrition Policy and Promotion as an online interactive dietary assessment tool for use by the public. Creation of PacTrac required several modifications to the IHEI, including a function to save data to allow for later access an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…The present research observed the importance of traditional prepared foods in the daily life of Filipino-Americans, such as adobo, lumpia , and pansit ; this finding has been previously documented. 27-28 The present investigation identified a number of food consumption practices among Filipino-Americans which may be used to develop a tailored FFQ. For example, commonly eaten Filipino foods that also contribute significantly to nutrient intakes might be added to a revised FFQ by adding foods to existing line items and by adding new line items.…”
Section: Discussionmentioning
confidence: 99%
“…The present research observed the importance of traditional prepared foods in the daily life of Filipino-Americans, such as adobo, lumpia , and pansit ; this finding has been previously documented. 27-28 The present investigation identified a number of food consumption practices among Filipino-Americans which may be used to develop a tailored FFQ. For example, commonly eaten Filipino foods that also contribute significantly to nutrient intakes might be added to a revised FFQ by adding foods to existing line items and by adding new line items.…”
Section: Discussionmentioning
confidence: 99%
“…During visit two, research staff reviewed the food log with the parents/caregivers (e.g., for completeness of food entries, portion size estimation, food preparation methods, and/or accuracy of recording data). Trained staff entered the food log data into the Pacific Tracker3 (PacTrac3), which includes a food composition database developed in collaboration with the University of Hawaii Cancer Center for use in the Pacific region [28][29][30]. For this study, PacTrac3 data were used to classify beverage type (i.e., sugar-sweetened beverages (SSB), milk, or water), fruit, and vegetable, as well as, calculate intake (e.g., cups/day, grams/day).…”
Section: Methodsmentioning
confidence: 99%
“…The Pacific Tracker 3 (PacTrac 3) is a web-based application that is a modification of the MyPyramid Tracker developed by the US Department of Agriculture’s Center for Nutrition Policy and Promotion (Martin et al, 2008). All dietary data from the FALs were entered using PacTrac 3.…”
Section: Methodsmentioning
confidence: 99%
“…After the first data entry at the jurisdiction sites, the FALs were sent to the Nutrition Support Shared Resource at the University of Hawai‘i Cancer Center for second review and data entry correction, as needed. Data from the PacTrac 3 were used to calculate food group, energy, and nutrient intakes using a food composition database developed by the University of Hawai‘i Cancer Center for use in the Pacific region (Murphy et al, 2006; Martin et al, 2008). …”
Section: Methodsmentioning
confidence: 99%